ANALISIS NILAI MORAL PADA CERPEN “SATE NANGKA” KARYA YUSNIAR - Kristiani, Erlis (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The short story "Sate Nangka" written by Yusniar is one of the literary works that can be used as motivation for readers and writers. The contents of this short story are very interesting because the contents of the story are common in everyday life. The problem formulation is focused on the moral values. The purpose of study to analyze moral value of the short story "Sate Nangka" written by Yusniar. The analysis in this study uses qualitative descriptive method. Qualitative descriptive method is a method that seeks to describe all symptoms or actual conditions at the time the research was carried out. Data collection is done by: (1) reading, (2) analyzing short stories, and (3) marking sentences in which there are moral values. The results showed that in the short story "Sate Nangka" by Yusniar, there are moral values related to daily life, such as: social care, creativity, hard work,  and no strings attached. Through this research, it is hoped that readers will be able to learn the moral values presented by the author in the short story "Sate Nangka" by Yusniar. Life experience that looks simple, but the impact is extraordinary for the character and it wiil be of the nation's children.